2011
DOI: 10.1136/jramc-157-04-03
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Outcome of UK Military Personnel Who Received a Massive Transfusion in Afghanistan During 2009

Abstract: The use of the current MTP was associated with a high rate of survival. Survivors require a continuity of critical care with a median demand for 3 days. The early use of plasma and platelets can be successfully delivered in the battlefield despite operational and logistic constraints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…3. An audit of outcomes for 59 UK military patients receiving massive transfusion in Afghanistan in 2009 would seem to support this approach, with an 86% overall rate of survival and five of seven patients who received transfusions over of 100 donor units subsequently surviving to hospital discharge [2]. Some authors have questioned the evidence for the highest ratios of FFP:PRBC, and have suggested that the optimal empirical ratio may be closer to 1:2 [24].…”
Section: Haemostatic Resuscitationmentioning
confidence: 99%
See 2 more Smart Citations
“…3. An audit of outcomes for 59 UK military patients receiving massive transfusion in Afghanistan in 2009 would seem to support this approach, with an 86% overall rate of survival and five of seven patients who received transfusions over of 100 donor units subsequently surviving to hospital discharge [2]. Some authors have questioned the evidence for the highest ratios of FFP:PRBC, and have suggested that the optimal empirical ratio may be closer to 1:2 [24].…”
Section: Haemostatic Resuscitationmentioning
confidence: 99%
“…A search of this database from 1 April 2008 to 30 March 2010 identified that 27% of casualties required a blood transfusion with 11% receiving 10 or more units of PRBCs [3]. A review of UK military personnel who received a massive transfusion in Afghanistan during 2009 showed that the mean blood component use per patient was approximately 22 units and that 12% received more than 100 units [2]. The UK military base the management of these casualties around damage control resuscitation (DCR).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exclusion criteria were studies on medical advances that had been made in civilian practice or those that focused on the transfer of information from civilian to military systems. Eight studies were found relevant to the area of analysis and reviewed in depth [10][11][12][13][14][15][16][17] (Table 1). A large number of publications described the potential for military developments to be transferred to civilian practice, but none were specifically relating military advances in trauma care to developing healthcare systems.…”
Section: Methodsmentioning
confidence: 99%
“…25,26 Aggressive treatment of the 'lethal triad' of hypothermia, acidosis and coagulopathy using haemostatic techniques, early damage control surgical intervention and massive transfusion has led to survival rates in military settings of over 86% compared to 40-60% in comparable trauma in civilian settings. 10 Adoption of these transfusion practices in civilian high-income trauma care 23 has been relatively slow. Applying military transfusion protocols to the civilian context has been complex as practices need to be adapted to the severity of the trauma and cannot rely on a uniform response to haemostatic resuscitation.…”
Section: Key Technologies: Intraosseous Needles Tourniquet and Bloodmentioning
confidence: 99%